60.7k views
5 votes
Thanks for the help pt.1​

Thanks for the help pt.1​-example-1
User Elithrar
by
5.8k points

2 Answers

5 votes
(jk)(x)= j (k(x)) = j(9-2x)

= -7(9-2x) = -63 + 14x

but i see there is no such option. may be second option is typo.

so you can select 2nd option
User Mike Woodhouse
by
6.3k points
3 votes

Answer:

The correct answer is
(jk)(x) = -63+14x.

Explanation:

We are given the following two functions,
j ( x ) = - 7 x and
k ( x ) = 9 - 2 x and we are to find the value of
( j k ) ( x ).

Applying the function j on function k to get:


(jk)(x) = -7(9-2x)


(jk)(x) = -63+14x

User Jasisz
by
5.9k points